PENGARUH KUALITAS PRODUK DAN PELAYANAN BA (Beauty Advisor) TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN PRODUK WARDAH (STUDI KASUS KONSUMEN LOTTEMART KUNINGAN CITY) - Zulher Zulher (Fakultas Ekonomi Universitas Borobudur, 2019)
This study aims to determine the extent of the influence of product quality and beautyadvisor services on customer satisfaction and its impact on consumer loyalty of wardah productsto visitors to LotteMart Kuningan City Jakarta.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 100 people. Data processing method uses the path analysismethod (Path Analysis) with the help of SPSS version 23.0. Statistical testing uses the individualparameter significance test (t test) and simultaneous significance test (F test).The results showed that simultaneously Product Quality, Bauty Advisor Service andCustomer Satisfaction significantly influence Consumer Loyalty. Partially shows that theanalysis: (1) Product Quality variables significantly influence Consumer Loyalty, while analysis(2) Bauty Advisor Service variables significantly influence Consumer Loyalty and on the analysis,(3) Customer Satisfaction variables significantly influence Consumer Loyalty.Keywords: Product Quality, Service, Customer Satisfaction, Loyalty Consumer.